Portrait of a Modern Manager in the Context of Information Management Systems of the Company - S. F. Miksjuk (Цифровая трансформация, 2017)
The article systematizes the management functions in the context of corporate information systems (CIS) with the selection of the set of tasks and the system of indicators in the context of each function. Problems of the practical use of CIS by managers of Belarusian enterprises are formulated and the qualification requirements for managers of CIS within the implemented functions are substantiated.